Evaluation of genetic diversity among Saudi Arabian and Egyptian cultivars of alfalfa (Medicago sativa L.) using ISSR and SCoT markers. Issue 1 (31st December 2023) - Alzahrani, Othman R.; Alshehri, M. Ali; Alasmari, A.; Ibrahim, S. D.; Oyouni, Atif A.; Siddiqui, Zahid H.
Abstract : Medicago sativa (Alfalfa) is valued for its high nutrient content as livestock feed for the production of dairy and meat products globally. The genetic improvement of alfalfa is limited because it is an allogamous autotetraploid. In this study, Inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) markers were used to assess the extent of genetic divergence between sixteen cultivars: twelve from Saudi Arabia and four from Egypt. The genetic diversity was assessed using eleven ISSR and eight SCoT primers. The ISSR primers produce 163 amplified bands with an average of 14.82 bands per primer and 60% polymorphism. The SCoT primers reveal 150 bands, with an average of 18.75 bands per primer and 77% polymorphism. The dendrogram clustered the Saudi and Egyptian cultivars into two distinct populations. The information revealed here will help in the breeding program of alfalfa, which will produce more drought tolerant and high-yielding varieties.